Effect of the roll stud diameter on the capacity of a high-pressure grinding roll using the discrete element method. (1st August 2020) - Nagata, Yu; Tsunazawa, Yuki; Tsukada, Kouji; Yaguchi, Yuichi; Ebisu, Yosuke; Mitsuhashi, Kohei; Tokoro, Chiharu
Graphical abstract: Highlights: The DEM with a breakage model was applied to HPGR grinding. The effect of the stud diameter on capacity was investigated and evaluated. A smaller stud produced a larger working roll gap during HPGR grinding. The stud diameter had less effect on throughout and power during HPGR grinding. The DEM with a breakage model is an effective tool for the roll design of the HPGR. Abstract: The high-pressure grinding roll (HPGR) is a type of roller mill that continuously produces particle-bed comminution. Since the capacity of the HPGR is determined by not only operating conditions but also the roll geometry, knowledge of the effectiveness of the roll geometry is still limited. This study investigated the effect of the stud diameter on the capacity of a stud-type HPGR using the discrete element method with a breakage model. To evaluate the effect of a stud diameter, which is placed on a roll surface, simulations were performed for three types of HPGR having 13-, 6-, and 3.75-mm studs. Simulation results show that the working roll gap increased when a smaller stud was used. This suggests that a roll surface with a smaller stud was likely to provide a stronger force. As a consequence, roll back likely occurred when a smaller stud was used because stronger friction acted on the roll surface. Meanwhile, the stud diameter had less effect on throughput and power during grinding. These trends obtained in simulation qualitatively correspond to those obtained in experiments. Consequently, the study demonstrated that simulation adopting the discrete element method with a breakage model can contribute to the investigation of the effect of roll design in an efficient HPGR grinding.